Effectiveness of Extreme Poverty Alleviation Implementation in Meranti Islands Regency - Setiawan, Rizky; Asrinaldi, Asrinaldi; Andrianus, Fery; Putera, Roni Ekha (UIR Press, 2026)
Poverty alleviation is a key global agenda for 2030. This action plan was agreed upon by 189 countries in the Sustainable Development Goals (SDGs). A problem that has emerged across all countries is the ineffectiveness of policies implemented in poverty alleviation programs. The extreme poverty target of zero percent in the 2024 government policy has not yet been achieved, according to data from the Indonesian Central Bureau of Statistics (BPS), there are still 0.29 percent of the population in extreme poverty. Phenomena found in poverty alleviation include the distribution of financial assistance and basic needs that are not on target and different poverty data between related stakeholders. This paper aims to examine the extent to which policies and programs in poverty alleviation. In this paper, the author uses the concept proposed by S.P. Siagian regarding effectiveness. The measuring tools for the success of a policy or program are objectives, strategies, infrastructure, analysis, formulation, planning, and supervision. This research was conducted in the Meranti Islands Regency because the Regency in Riau Province still has a population of extreme poverty. The research method uses a systematic literature review by collecting previous research data, both primary and secondary.